The Use of Water, Food and Cover by Javan Rhino (Rhinoceros sondaicus, desmarest 1822) and Banteng (Bos javanicus, d'Alton 1832) at Cikeusik and Citadahan, Ujung Kulon National Park - Suryo Suhono; E.K.S Harini Muntasib (Media Konservasi, 2001)
Javan Rhino (Rhinoceros sondaicus, Desmarest 1822) and Banteng (Bos javanicus, d'Alton 1832) live sympatric in Ujung Kulon National Park. Both of them have some similarities such as food preferences, shelter preferences, and water dependent. Banteng could act as a threat to Javan Rhino if there is lack of natural resources availability such as in dry season. There is a few of similarity in water need, though Javan Rhino and Banteng both need fresh water everyday. Javan rhino and Banteng also have high preference on a few plant species in Ujung Kulon. The interaction between Javan Rhino and Banteng at Cikeusik and Citadahan is the form of indirect competition called exploitative competition.